IMPLEMENTATION OF THE REGULATION OF THE NATIONAL POLICE CHIEF NUMBER 13 OF 2016 CONCERNING INTERNAL SECURITY (PAMINAL) FOR MEDAN POLICE PERSONNEL - Muhammad Adi Putra; Isnaini Isnaini; M. Ridha Haykal Amal (SOSIOEDUKASI, 2026)
This study aims to analyze the implementation of Police Regulation (Perkap) No. 13 of 2016 concerning Internal Security (Paminal) at Polrestabes Medan, focusing on its effectiveness in preventing disciplinary violations and identifying optimization strategies. The research employs a juridical-normative method with a descriptive-analytical approach. Data were collected through documentary analysis of relevant legal regulations and interviews to obtain an empirical overview of field conditions. The findings reveal that although the regulation provides a clear legal structure and comprehensive normative framework, its implementation remains suboptimal. A gap persists between law in the books and law in action, influenced by internal legal culture, misplaced corporate solidarity, and structural limitations. Enforcement is constrained by limited personnel, inadequate specialized competence, restricted independence, and insufficient infrastructure. Efforts to optimize implementation include capacity building, strengthening integrity values, and enhancing transparency. Sustainable improvement, however, requires strong leadership commitment and long-term transformation of internal legal culture.